2017
DOI: 10.1101/199380
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Expectation-induced modulation of metastable activity underlies faster coding of sensory stimuli

Abstract: 1Sensory stimuli can be recognized more rapidly when they are expected. This 2 phenomenon depends on expectation affecting the cortical processing of sensory 3 information. However, virtually nothing is known on the mechanisms responsible for 4 the effects of expectation on sensory networks. Here, we report a novel computational 5 mechanism underlying the expectation-dependent acceleration of coding observed in 6 the gustatory cortex (GC) of alert rats. We use a recurrent spiking network model with a 7 cluster… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
148
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(163 citation statements)
references
References 72 publications
15
148
0
Order By: Relevance
“…Expected stimuli can be recognized more rapidly than unexpected ones (Mazzucato et al, 2019;Pinto et al, 2015;Samuelsen et al, 2012;Sussman et al, 2016a). Top-down modulation of visual processing involves visual cortical areas, which is involved with object recognition, as well as parietal and prefrontal cortex, which is involved with visually guided movements and attentional control (Gilbert and Li, 2013).…”
Section: Fmri Data Acquisitionmentioning
confidence: 99%
See 2 more Smart Citations
“…Expected stimuli can be recognized more rapidly than unexpected ones (Mazzucato et al, 2019;Pinto et al, 2015;Samuelsen et al, 2012;Sussman et al, 2016a). Top-down modulation of visual processing involves visual cortical areas, which is involved with object recognition, as well as parietal and prefrontal cortex, which is involved with visually guided movements and attentional control (Gilbert and Li, 2013).…”
Section: Fmri Data Acquisitionmentioning
confidence: 99%
“…Relative to stimulus-driven bottom-up processes, top-down processes take into account cues or goals indicating upcoming threat-related stimuli. These anticipatory cues or goals may contribute to perceptual and attentional prioritization of threatening stimuli (Mazzucato et al, 2019;Yoshida and Katz, 2011). To determine the top-down and bottom-up mechanisms during the present emotion regulation task, we extracted the time courses from hub regions of the visual and visuospatial attention networks and observed that top-down anticipatory cues modulated the temporal dynamics of sensory coding and attention control.…”
Section: Top-down Guidance Of Threat-related Perception and Attentionmentioning
confidence: 99%
See 1 more Smart Citation
“…S7). One may drive clustered networks with strong time-dependent stimuli to pace activity along stimulus-specific sequences [12,21,25,26,68]. However, this would merely shift the problem of reliable sequence generation from the local circuit to an upstream area producing the specific input (but see [69]).…”
Section: Network Models Of Sequencesmentioning
confidence: 99%
“…Previous work showed that the activity patterns, revealed by hidden Markov models, can be interpreted as metastable attractors, arising from recurrent dynamics in local cortical circuits [12,21]. Metastable attractors are produced in biologically plausible network models [22,23] and have been used to elucidate features of sensory processing [12,21], working memory [24] and expectation [25], and to explain state-dependent modulations of neural variability [22,23,26]. However, while previous models are capable of generating sequential activity [21,[27][28][29], they are hindered by a fundamental trade-off between sequence reproducibility and trial-to-trial temporal variability.…”
Section: Introductionmentioning
confidence: 99%